Biocontrol of sheath blight and root‑knot nematode and growth promotion of rice plants by rhizobacteria - de Souza Júnior, Ismail Teodoro; Moura, Andrea Bittencourt; Schafer, Jaqueline Tavares; Correa, Bianca Obes; Gomes, César Bauer (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the compatibility between previously selected biocontroller rhizobacteria and the effect of their combination upon sheath blight (Rhizoctonia solani), root-knot nematode (Meloidogyne graminicola) and growth promotion in rice plants. The compatibility between these bacteria was determined by the overlay antibiosis. The effect of isolate combinations was evaluated by seed microbiolization of the rice cultivar El Paso L144 with rhizobacteria suspensions of DFs185 (Pseudomonas synxantha), DFs223 (P. fluorescens), DFs306 (unidentified), DFs416 and DFs418 (Bacillus sp.). These rhizobacteria were used alone or combined in arrangements of two, three and four isolates. The DFs223 isolate was not combined because it is incompatible with the other bacteria. Five rhizobacteria combinations (DFs185/418, DFs306/416, DFs306/418, DFs416/418, DFs185/306/418) and the isolate DFs306 stood out for reducing M. graminicola reproduction and promoting plant growth. Combination DFs185/306 presented the best results for the control of R. solani and for growth promotion. The DFs306/416 combination provided the best results for the control of the two diseases.